Seizure control during the COVID-19 pandemic: Correlating Responsive Neurostimulation System data with patient reports. (July 2022) - Karakas, Cemal; Ward, Ryan; Hegazy, Mohamed; Skrehot, Henry; Haneef, Zulfi
Highlights: We examined Responsive Neurostimulation (RNS)-detected seizures (long episodes) during the COVID-19 pandemic as a more reliable marker than patient self-reports. In contrast to prior literature, most patients did not have an increase in seizures. RNS-detected seizure counts did not correlate to patient self-reports of increased/worsened seizures. Abstract: Objective: To understand the impact of the Coronavirus Disease-2019 (COVID-19) pandemic on seizure frequency in persons with epilepsy with a Responsive Neurostimulation (RNS) system implanted. Methods: Weekly long episode counts (LEC) were used as a proxy for seizures for six months pre-COVID-19 and during the COVID-19 period. Telephone surveys and chart reviews were conducted to assess patient mental health during the pandemic. The change in LEC between the two time periods was correlated to reported stressors. Results: Twenty patients were included. Comparing the pre-COVID-19 period to the COVID-19 period, we found that only 5 (25%) patients had increased seizures, which was positively correlated with change in anti-seizure medications (ASM, p = 0.03) and bitemporal seizures (p = 0.03). Increased seizures were not correlated to anxiety (p = 1.00), depression (p = 0.58), and sleep disturbances (p = 1.00). The correlation between RNS-detected and patient-reported seizures was poor (p = 0.32). Conclusions: Most of our patients did not have an increase in seizures following the COVID-19 pandemic. Changes in ASM and bitemporal seizures were positively correlated to increased LEC. There was no correlation between pandemic-related stress and seizures in those found to have increased seizures. Significance: This is the first study correlating RNS-derived objective LECs with patient self-reports and potential seizure risk factors during the COVID-19 pandemic.